Алгоритм диагностирования software модуля - Хаханов, В. И.; Сушанов, А. В.; Давыдов, М. Д.; Литвинова, Е. И. (ХНУРЭ, 2008)
Software product testing methods based on disjunctive normal forms are offered. Normal forms represent fault coverage table.
Keywords: алгоритм диагностирования; software модуль